Development of “Si Panca" Based on Value Clarification to Implement Nationalism and Critical Thinking - Pasju, Nining; Hadiwinarto, Hadiwinarto (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of national education in shaping the character of the Indonesian nation is through the subjects of Citizenship Education (PKn). Instilling character values ??in the eyes of Citizenship Education (PKn) in schools must start early. This is very influential on the survival of students. Various improvement efforts have not achieved optimal results. Improvement efforts are needed to instill and think critically by using the application of Si Panca based on Value Clarification Technique (VCT). This study uses a quantitative approach with a population of 81 students. Based on the results of research on the impact of the application of Si Panca based on Value Clarification Technique (VCT). In this literature study, several things will be learned, including: Civics Learning, Si Panca Applications, Value Clarification Technique (VCT) Models. The results of the literature analysis show that the application of Si Panca based on Value Clarification Technique (VCT) can instill the character of love for the homeland and critical thinking skills.